Studi Toksikologi Lingkungan: Pengaruh Paparan Mikroplastik Terhadap Jumlah Leukosit Tikus Putih (Rattus norvegicus) - Dewi Yudiana Shinta; Melly Siska Suryani; Ikhwan Resmala Sudji; Muhammad Diki Juliandi; Merry Thressia; Herix Sonata MS (Pelantar Press, 2026)
Increasing microplastic pollution in the environment raises concern about toxic risks to living organisms, and one important health risk involves immune system disruption, which can be observed through changes in leukocyte counts. This study aims to analyze the effect of microplastic exposure on leukocyte numbers in white rats (Rattus norvegicus) as an early indicator of environmental toxicity and health risk. The research also seeks to provide scientific evidence that can support environmental management policies and human health protection strategies. An experimental design was applied in which rats were divided into one control group and several treatment groups, and each treatment group received oral microplastic exposure at different doses over a specific period while FTIR spectroscopy (Fourier Transform Infrared Spectroscopy) was used to characterize the microplastic particles before administration. After the exposure period, blood samples were collected and leukocyte counts were measured using a hematology analyzer, and statistical analysis was then performed to compare leukocyte levels across all groups. The results showed that rats exposed to microplastics exhibited increased leukocyte counts above the normal range during both week one and week two, and these elevated counts were observed across groups that received different doses of microplastics. The rise in leukocyte numbers indicates an inflammatory response and immunological stress caused by microplastic exposure, and furthermore, the findings suggest that microplastics not only produce toxic effects but also tend to accumulate and remain in the body for extended periods. In conclusion, microplastic exposure has a significant effect on leukocyte counts in white rats, and this effect reflects immune system disturbance and potential disruption of immunological homeostasis. Consequently, microplastics should be recognized as an important threat in environmental toxicology, and continued research and regulatory attention are necessary to address the risks that microplastics pose to both ecological systems and human health